THE SEMANTIC-PRAGMATIC DISTINCTION - Tuhtaeva Shahzoda Oktamovna (Лучшие интеллектуальные исследования, 2023)
Historically, the semantic-pragmatic distinction has been formulated in various ways. These formulations have fallen into three main types, depending on which other distinction the semantic-pragmatic distinction was thought most to correspond to:  linguistic (conventional) meaning vs. Use  truth-conditional vs. non-truth-conditional meaning  context independence vs. context dependence